ANALISIS BAHAN AJAR AL-QARI AL-A’RABIY - Ahmad Rizki Nugrahawan; Amin Fauzi (Universitas Muhammadiyah Prof Dr Hamka, 2021)
This research aims to identify and to ensure the advisability of Arabic book module “Qary el-A’raby 3rd” published by Indonesia Lafazh Book. The book is a teaching materials for the sixth grade of Elementaryy school of Bani Saleh Labschool. The Researcher uses the descriptive kualitative method to analyze the contents of the book module as a total population according to some certain criteria and indicators. The research shows that the book module is proper to be taught in the sixth grade of Bani Shaleh elemantary school indicated by 95% of indicator values.